The Influence of Fintech User’s Attitudes on Selection Through Fintech Users Interest in Millenial Generation of the City of Makassar - Agatha Cristy Situru; Syamsu Alam; Andi Reni (Magister Management, Hasanuddin University, 2020)
The research aimed to analyze the influences of the peer to peer lending, risk and investment management, and payment, the users' interests on the fintech type selection. Data were collected through the questionnaire which was processed using the path analysis. The hypothesis test used the simultaneous test (f), partial test (t), and the Sobel test. The result of the analysis indicates that the peer-to-peer lending and payment variables have a significant influence, whereas the risk and investment management variables do not have a significant effect. The path analysis result of the first equation namely the peer-to-peer lending variables has a positive effect, the risk and investment management variable has a positive influence, and the payment variable has a positive effect. The T result in the second equation namely the peer-to-peer lending variable has a positive influence, the risk and investment management variable has a positive effect, the payment variable has a positive influence, and the user’s interests have a positive effect. Sobel’s test result indicates that the users’ interest can mediate the relationship between the peer to peer lending and Fintech type selection, the users’ interests cannot mediate the relationship between the risk and investment management, and Fintech type selection and users’ interests cannot mediate the relationship between the payment and Fintech type selection